Determinants of Rice Farmers' Utilization of Agricultural Information in Central Thailand. Issue 1 (2nd January 2017) - Aonngernthayakorn, Kijsart; Pongquan, Soparth
ABSTRACT: This study investigated factors affecting the utilization of agricultural information among rice farmers in central Thailand. About 240 rice farmers in the Bang Pla Ma District of Suphanburi Province were surveyed and interviewed to describe how they utilize agricultural information. Respondents were divided into small, medium, and large rice farmers according to farm size. Small farmers had more access to information on farming practices and postharvesting activities, while large and medium farmers utilized more information on marketing, covering future market and farmgate prices. The multinomial logit model showed that length of farming experience, household labor size, distance to the Rice Research Center, and number of information sources, as well as access to the Internet, television, extension program, and relatives, significantly influence farmers' utilization of agricultural information.